Peran resource dan vulnerability index of resilience terhadap distres psikologis remaja saat pandemi Covid-19 - Ni Putu Putri Puspitaningrum; Sri Redatin Retno Pudjiati (University of Muhammadiyah Malang, 2021)
Changes that occur rapidly during a pandemic are prone to causing psychological distress in adolescents. Therole of resources and the vulnerability index of resilience need to be explored as variables that affect psychologicaldistress. This study used a quantitative design with 111 adolescents who were collected online. Data were processedusing descriptive and correlation-regression analysis. The resource index has a negative effect of 12.6 %, while thevulnerability index has a positive effect of 21.2 % on psychological distress. The interaction of both indexes has a rolein psychological distress (R2= 0.21,F= 14.50,ρ= 0.000). Other findings indicate that participant psychological distress is high, with an average resource and a low vulnerability index. This study found that the higher the resourceindex, the lower psychological distress. Conversely, the higher the vulnerability index, the higher the psychologicaldistress. Intervention needs to be done by targeting both resilience indexes.